Little miss tiny - Hargreaves, Roger (World International Great britain, 1990)
"Little Miss Tiny" is one of the characters from the popular Mr. Men and Little Miss series by Roger Hargreaves. Little Miss Tiny is a very small character, even smaller than the other Little Miss characters. She$1 (Bs often portrayed as being so tiny that she has to be extra careful to avoid being overlooked or getting into trouble. Despite her size, she shows that even the smallest people can make a big difference when they use their unique qualities in positive ways.s